Energy efficiency index as an indicator for measuring building energy performance: a review - Abu Bakar, Nur Najihah (Elsevier, 2015)
Accurate forecasting of energy consumption in a building is an important strategy in achieving the goal of reducing energy demand, as well as to improve energy efficiency. To implement this strategy, many methods and indicators have been proposed to monitor and measure energy performance in buildings. However, various factors that influence energy consumption of a building system operation, such as the types of activities carried out in the building, weather conditions, building materials, HVAC system and occupancy; contribute to the difficulty in accurately measuring a buildings energy system. This paper provides a review on the Energy Efficiency Index (EEI) as an indicator used to track the performance of energy consumption in a building. Previous research works concerning this index and relevant mathematical models are also introduced. Other related methods or indicators for measuring energy consumption performance of buildings will also be presented.